Procuring Guilty Pleas for International Crimes: The Limited Influence of Sentence Discounts - Combs, Nancy A. (2006)
Approximately 90 percent of all American criminal cases are disposed of by means of guilty pleas, and a large percentage of defendants brought before courts in England, Australia, and other countries that use common-law procedures likewise plead guilty. Why do substantial numbers of defendants in national criminal justice systems choose to convict themselves when they are entitled to have their guilt formally adjudicated? The widely accepted primary reason is that they receive sentencing discounts when they choose to selfconvict. Most defendants charged with domestic crimes plead guilty following a process of plea bargaining between defense counsel and prosecutors. Although plea bargaining can take many forms, at its heart is a promise of some form of sentence leniency in exchange for the defendant's guilty plea. In the context of domestic crimes, then, most defendants are understood to plead guilty primarily, if not exclusively, in order to obtain sentence discounts, and the magnitude of the available discounts will largely determine how many guilty pleas will be obtained